2017
DOI: 10.1016/j.celrep.2017.05.090
|View full text |Cite
|
Sign up to set email alerts
|

Reliable and Elastic Propagation of Cortical Seizures In Vivo

Abstract: Mapping the fine-scale neural activity that underlies epilepsy is key to identify potential control targets of this frequently intractable disease. Yet, the detailed in vivo dynamics of seizure progression in cortical microcircuits remain poorly understood. We combine fast two-photon calcium imaging (30-Hz) with LFP recordings to map, cell by cell, the spread of locally induced (4-AP or picrotoxin) seizures in anesthetized and awake mice. Using single-layer and microprism-assisted multi-layer imaging in differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

21
120
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(152 citation statements)
references
References 72 publications
21
120
4
Order By: Relevance
“…Consistently, power spectrum and current source density analyses indicated the possible involvement of the granular neocortical layer that receives afferent connections from the thalamus. In addition, our data indicated the participation of supragranular and infragranular layers, hence suggesting an alternative and nonexclusive intracortical mechanism where epileptiform activity would propagate through horizontal pathways, as proposed previously . Whatever their mechanism(s), discharges were rarely detected—and not in all KO pups.…”
Section: Discussionsupporting
confidence: 79%
“…Consistently, power spectrum and current source density analyses indicated the possible involvement of the granular neocortical layer that receives afferent connections from the thalamus. In addition, our data indicated the participation of supragranular and infragranular layers, hence suggesting an alternative and nonexclusive intracortical mechanism where epileptiform activity would propagate through horizontal pathways, as proposed previously . Whatever their mechanism(s), discharges were rarely detected—and not in all KO pups.…”
Section: Discussionsupporting
confidence: 79%
“…Whereas at the site of seizure onset recruitment of supra‐ and infragranular layers showed diverse recruitment dynamics patterns, with rapid synchronous recruitment of layer 2/3 and 4 neurons versus sluggish asynchronous recruitment of layer 5 PNs, propagated seizures showed uniform recruitment dynamics in all layers, consisting of a gradually spreading pattern, with layer 2/3 preceding layer 5 recruitment. Importantly, in contrast to our study, Wenzel at al did not record from INs, and thus the relative recruitment dynamics of PNs and INs during seizure propagation was not studied.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our findings, a previous study that also used in vivo 2‐photon calcium imaging of GCaMP6‐expressing neurons to study propagation of in vivo 4AP‐ and PTX‐induced neocortical seizures reported neocortical seizures that initially propagated in the supragranular layers and only later involved the infragranular layer. They further found that PV‐expressing INs controlled the propagation pattern of these seizures . In contrast to this study, we concentrated on seizure initiation, specifically at the site of seizure onset, or at least in close proximity to it.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations